ANALISA EKSERGI PADA PRODUKSI NITROGEN SISTEM PRESSURE SWING ADSORPTION (PSA) - Syakdani, Adi (Politeknik Negeri Sriwijaya, 2018)
Nitrogen is staple compound in the chemical industry. Nitrogen demand continues to increase every year. Indonesia's nitrogen demand reaches 6% of world demand, and this number is expected to continue to increase. Increased nitrogen demand will also require high nitrogen production. In the production of nitrogen the most commonly used method is cryogenic systems. But in this way a lot of energy is wasted, especially in the conversion process. In an effort to use energy efficiently, non-cryogenic nitrogen production systems were developed. One of them is the Pressure Swing Adsorption (PSA) system, which applies the principle of adsorption.. Factors that may affect the purity of the product are the adsorbate pressure (air) and the adsorbate contact time and the adsorbent. Adsorbent used is Carbon Molecular Sieve (CMS). Compressed air is obtained from the compression process by a compressor that uses electricity as the primary power source. In an effort to optimize the use of energy used, the adsorbat pressure varied from 4.5.6 and 7 bar, while the contact time was varied 1.3. and 5 minutes. Based on the results of the study the most optimal operating conditions have been carried out to produce high nitrogen purity at 4 bar pressure and 5 minutes contact time and the resulting nitrogen purity is 96.2%.The optimum condition of exergy efficiency is 7 bar at 1 minute contact time with 97.079% exergy efficiency. While for the compressor the highest compressor efficiency and the lowest Irreversibility that is at the pressure of 7.1 bar that is efficiency 78.925% and Ic 14.951 kJ/kg